Education after empire: A biopolitical analytics of capital, nation, and identity. Issue 7 (7th June 2022) - Means, Alexander J.; Ida, Yuko
Abstract: As it emerged in the late twentieth century, Empire promised a new era of global cooperation and stability through a seamless integration of late capitalism and neoliberal technocracy. Premised as an end to history itself, all that was left to accomplish was to tinker at the margins, stimulate corporate enterprise, embrace financialization and technological innovation, and encourage liberal rights and inclusion. As we enter the third decade of the twenty-first century, the narrative fictions sustaining Empire have broadly collapsed at the level of symbolic identification and belief. Empire has entered into a period of global emergency and mutation. Engaging with Michael Hardt and Antonio Negri's work, this paper considers what might emerge when we read education into the circuitry of Empire's decay. First, we locate Empire within foundational tensions in modernity, using Kantian philosophy and colonialism as examples, to foreground the idea of education as immanent to historical processes of creativity, resistance, and innovation. Second, we highlight dead-end responses, from space colonization to neo-fascism, as representations of how modes of education circulate to stabilize and contain Empire's crises, specifically in relation to capitalism, nationalism, and identity. Lastly, the paper develops a political ontology of education after Empire.